AI-Driven Sharia Financing Transformation: Digital Governance and Sharia Compliance Challenges at FIF GROUP Indonesia - Azkia Ahilatu Syifa; Saifudin; Irfan Musonif; Maskur Rosyid (FEBI IAIN Langsa, 2026)
The rapid advancement of digital technology has accelerated the transformation of Islamic financing institutions toward more efficient and data-driven services. However, the implementation of Artificial Intelligence (AI) in Islamic financing raises challenges related to digital governance, Sharia compliance, algorithmic transparency, and ethical accountability. Existing studies mainly focus on Islamic banking and fintech, while limited attention has been given to AI implementation in non-bank Islamic financing institutions in Indonesia. This study aims to analyze the role of AI in supporting digital transformation at FIFGROUP Indonesia, particularly through its Sharia financing unit, AMITRA, and to examine the resulting Sharia governance challenges. This study uses a qualitative documentary study approach with a normative and socio-legal approach. Data were collected through document analysis of financial regulations, DSN-MUI fatwas, academic literature, annual reports, and digital financing practices implemented by FIFGROUP. The data were analyzed thematically to identify the implications of AI adoption in Sharia financing services. The findings indicate that AI improves operational efficiency, customer service automation, risk assessment accuracy, fraud detection, and transaction transparency. However, AI implementation also creates challenges related to algorithmic opacity, digital gharar (uncertainty), data privacy, and the validity of electronic contracts. This study argues that explainable AI, human oversight, and adaptive Sharia governance are essential to ensuring that digital financing practices remain aligned with the principles of justice, transparency, and maqāṣid al-sharī‘ah.